Effect of dry machining on tool wear - Madihah, Zubir (2012)
This thesis presents the wear of coated carbide insert in machining carbon steel AISI 1065. Machineability of AISI 1065 is considered good with high strength, high resistance to breakage and high modulus of elasticity. This has increased the tool wear of the coated carbide when it is used to machining of AISI 1065. The main objective of this project is to examine the progress of tool wear, identify the interaction between the different parameters and to find out the optimal parameter that can be used in dry machining. In this project, 33 full factorial design of experiments (DOE) was employed in STATISTICA software to plan and perform the experiment systematically so that any possible experimental error would be minimized. Machining variables considered are cutting length, cutting speed and feed rate. The variables for there levels were 90, 120 and 150 rev/min for cutting speed, 0.13, 0.18, 0.22 mm/rev for the feed rate and 0.8, 1.0, and 1.2 mm for depth of cut respectively. Machining AISI 1065 was carried out by using the conventional lathe machine. The work piece is been turning for 7 rounds for each turning process. After 7 rounds of turning process, wear of the coated carbide insert was investigated and measured by using Microscope MarVision MM320 and Quadra check 300. Experimental data was analyzed in STATISTICA. Analysis of variance (ANOVA) is done to identify the most influencing parameters in this research. From the ANOVA analysis, the cutting speed and the feed rate are the most significant parameter that influencing tool wear. Depth of cut effect can be negligible. The minimum tool wears is at the lowest cutting speed that is 90rev/min and at lowest feed rate 0.13mm/rev.